The association of vaccination status with perceived discrimination in patients with COVID-19: results from a cross-sectional study (Swiss Medical Weekly, 2024)
STUDY AIMS: During the COVID-19 pandemic, there was increasing pressure to be vaccinated to prevent further spread of the virus and improve outcomes. At the same time, part of the population expressed reluctance to vaccination, for various reasons. Only a few studies have compared the perceptions of vaccinated and non-vaccinated patients being treated in hospitals for COVID-19. Our aim was to investigate the association between vaccination status and perceived healthcare-associated discrimination in patients with COVID-19 receiving hospital treatment.METHODS: Adult patients presenting to the emergency department or hospitalised for inpatient care due to or with COVID-19 from 1 June to 31 December 2021 in two Swiss hospitals were eligible. The primary endpoint was patients’ perceived healthcare-associated discrimination, measured with the Discrimination in Medical Settings (DMS) scale. Secondary endpoints included different aspects of perceived quality of care and symptoms of psychological distress measured with the Hospital Anxiety and Depression Scale.RESULTS: Non-vaccinated patients (n = 113) had significantly higher DMS scores compared to vaccinated patients (n = 80) (mean: 9.54 points [SD: 4.84] vs 7.79 points [SD: 1.85]; adjusted difference: 1.18 [95% CI: 0.04–2.33 points]) and 21 of 80 vaccinated patients felt discriminated against vs 54 of 113 non-vaccinated patients (adjusted OR: 2.09 [95% CI: 1.10–3.99 ]). Non-vaccinated patients reported lower scores regarding respectful treatment by the nursing team (mean: 8.39 points [SD: 2.39] vs 9.30 points [SD: 1.09]; adjusted difference: –0.6 [95% CI: -1.18 – –0.02 points]).CONCLUSION: We found an association between vaccination status and perceived healthcare-associated discrimination. Healthcare workers should act in a professional manner regardless of a patient’s vaccination status; in doing so, they might prevent the creation of negative perceptions in patients.